Effect of hemodialysis on short-term outcomes after colon cancer surgery - Toshio Shiraishi; Tetsuro Tominaga; Takashi Nonaka; Shintaro Hashimoto; Kiyoaki Hamada; Masato Araki; Yorihisa Sumida; Hiroaki Takeshita; Hidetoshi Fukuoka; Hideo Wada; Kazuo To; Mariko Yamashita; et al. (PLoS ONE, 2022)
Background Hemodialysis patients who undergo surgery have a high risk of postoperative complications. The aim of this study was to determine whether colon cancer surgery can be safely performed in hemodialysis patients. Methods This multicenter retrospective study included 1372 patients who underwent elective curative resection surgery for colon cancer between April 2016 and March 2020. Results Of the total patients, 19 (1.4%) underwent hemodialysis, of whom 19 (100%) had poor performance status and 18 had comorbidities (94.7%). Minimally invasive surgery was performed in 78.9% of hemodialysis patients. The postoperative complication rate was significantly higher in hemodialysis than non-hemodialysis patients (36.8% vs. 15.5%, p = 0.009). All postoperative complications in the hemodialysis patients were infectious type. Multivariate analysis revealed a significant association of hemodialysis with complications (odds ratio, 2.9362; 95%CI, 1.1384–7.5730; p = 0.026). Conclusion Despite recent advances in perioperative management and minimally invasive surgery, it is necessary to be aware that short-term complications can still occur, especially infectious complications in hemodialysis patients.